Region II Meeting in Los Angeles - James C. Basile:::::: (1962)
Memo from James C. Basile, 37th Assembly District Representative, that reports on the April 3, 1962 caucus meeting of Region XX (Los Angeles, Ventura, and Santa Barbara counties) of the California Democratic Council (CDC). The meeting was held in Los Angeles and primarily focused on preparing for the CDC Board of Directors meeting in Fresno on April 6–8.